Contrast Relationships Between Arctic Oscillation and Ozone in the Stratosphere Over the Arctic in Early and Mid‐to‐Late Winter. Issue 5 (9th March 2021) - Liu, Meichen; Hu, Dingzhu
Abstract: Previous studies paid more attention on the winter‐mean relationship between the surface Arctic Oscillation (AO) and stratospheric ozone over the Arctic. However, few studies focused on the subseasonal relationship between the stratospheric ozone and surface AO in boreal winter. We investigated the subseasonal relationship between the AO and stratospheric ozone over the Arctic in each boreal winter month during 1980–2017 that is independent on the El Niño–Southern Oscillation and Quasi‐Biennial Oscillation signals using Modern‐Era Retrospective Analysis for Research and Applications version 2 reanalysis data sets. Results showed that the positive AO phases correspond to two negative anomalous ozone centers located in the middle stratosphere (∼30 hPa) and upper troposphere–lower stratosphere over the Arctic in each month. There is an in‐phase relationship between the AO and the Arctic ozone at 70–100 hPa in December, which is opposite to the out‐of‐phase relationship between these two metrics in mid‐to‐late winter. In December, the subtropical jet in the Pacific under the positive AO phase shifts poleward with strengthened planetary wavenumber‐2 waves in the lower stratosphere. The strengthened wavenumber‐2 wave flux contributes to the positive ozone anomalies at 70–100 hPa via modifying the asymmetric component of polar vortex. However, in January and February, the subtropical jet weakens during the positive AO years, along with less planetary wavenumber‐1 waves propagating into the Arctic lower stratosphere. This weakened wavenumber‐1 wave tends to result in the negative ozone anomalies via weakening the downwelling branch of Brewer–Dobson circulation and strengthening the stratospheric Arctic vortex. Key Points: The relationship between the Arctic ozone in the lower stratosphere and AO in December is in‐phase, opposite to that in mid‐to‐late winter There are positive ozone anomalies in December during the positive AO years, which are related to the asymmetric part of polar vortex In mid‐to‐late winter, the linkage of the ozone with the AO mainly depends on Brewer–Dobson circulation and intensity of polar vortex